Pemanfaatan Aplikasi Canva sebagai Inovasi Media Pembelajaran dalam Meningkatkan Hasil Belajar PAI Siswa MTs Al-Qur’aniyah - Amin, Alfauzan; Suranda, Novalyo (MODELING: Jurnal Program Studi PGMI, 2024)
This research aims to analyze the use of the Canva application in improving the learning outcomes of Class IX students at MTS Al-Qur'aniyah. This research uses Mixed Methods research. Research Results: Canva is an online design program that provides various tools such as presentations, resumes, posters, pamphlets, brochures, graphics, infographics, banners, bookmarks, bulletins, and others. Proper use of Canva learning media will help in creating effective, efficient and interesting learning programs so that it can improve student learning outcomes. Based on the results of the questionnaire calculations obtained, before using the Canva application media in the form of power points, the results were 75%, as many as 30 students were not able to understand the material, 20% (standard) as many as 8 students were quite able to understand the material, and 5% as many as 2 participants students are able to understand the material, and 0 percent are very able to understand the material. After using the Canva application, the results were 80%, 32 students were very able to understand the material, 15%, 6 students were able to understand the material, and 5%, 2 students were quite able to understand the material, and 0 percent were not able to understand the material. This shows that the Canva application has a big influence on improving the learning outcomes of Class IX students at MTS Al-Qur'aniyah. Abstrak Penelitian ini bertujuan untuk menganalisa Pemanfaatan Aplikasi Canva Dalam meningkatkan hasil belajar siswa Kelas IX di MTS Al-Qur’aniyah. Penelitian ini menggunakan jenis penelitian Mixed Methods. Hasil Penelitian: Canva sebagai suatu program desain online yang menyediakan bermacam peralatan seperti presentasi, resume, poster, pamflet, brosur, grafik, infografis, spanduk, penanda buku, bulletin, dan lainnya. Penggunaan media pembelajaran canva secara tepat akan membantu dalam menciptakan program pembelajaran yang efektif, efisien dan menarik sehingga dapat meningkatkan hasil belajar peserta didik. Berdasarkan hasil perhitungan angket yang diperoleh, sebelum penggunaan media aplikasi canva berupa power point di dapatkan hasil sebesar 75% sebanyak 30 peserta didik Tidak Mampu memahami materi, 20% (standar) sebanyak 8 peserta didik Cukup Mampu memahami materi, dan 5% sebanyak 2 peserta didik Mampu memahami materi, dan 0 persen Sangat Mampu memahami materi. Setelah penggunaan aplikasi canva diperoleh hasil 80% sebanyak 32 peserta didik Sangat Mampu memahami materi, 15% sebanyak 6 peserta didik Mampu memahami materi, dan 5% sebanyak 2 peserta didik Cukup Mampu memahami materi, dan 0 persen Tidak Mampu memahami materi. Hal ini menunjukkan bahwa Aplikasi Canva sangat mempengaruhi peningkatan hasil belajar peserta didik Kelas IX di MTS Al-Qur’aniyah.